Reaching cancer survivors where they are : effects and experiences of live-remote exercise - Melissa Kotte (2025)
The number of cancer survivors is steadily increasing, yet many experience impaired health outcomes and reduced health-related quality of life. Exercise has been shown to provide important benefits for cancer survivors, including improvements in health-related quality of life. Despite this evidence, physical activity levels remain low, partly due to individual barriers such as treatment- related side effects, lack of time, and distance, as well as limited availability of suitable services. This highlights the need to develop accessible exercise programmes. Supervised, virtually delivered exercise has the potential to overcome such barriers by extending reach while maintaining professional support. However, evidence regarding the efficacy of this delivery format, and survivors' experiences of exercising in this context, remains limited. The overall aim of this thesis was to evaluate the effects of a live-remote exercise intervention for survivors of breast, prostate, and colorectal cancer, and to explore participants' experiences of exercising in this format, in order to inform the development of accessible exercise programmes that support healthy survivorship.Study I evaluated the effects of a live-remote exercise intervention in individuals who had completed curative treatment for breast, prostate, or colorectal cancer. In this randomised controlled trial, 200 participants were allocated to either usual care or a 12-week live-remote exercise intervention. In small groups of up to eight, participants exercised twice weekly for 60 minutes under the virtual supervision of an upskilled personal trainer. The results showed no significant effect on overall health-related quality of life. However, significant improvements were observed in physical activity levels, physical functioning, cardiorespiratory fitness, and upper body strength post-intervention, although most effects were not maintained at the six month follow-up.Study II explored which subgroups of cancer survivors benefited most from the intervention by conducting an exploratory subgroup analysis of the trial data from Study I. Demographic and clinical characteristics, including age, sex, body mass index, cancer type, chemotherapy, and endocrine therapy, were examined as potential moderators of intervention effects, alongside baseline health status. The results suggested that sex and endocrine therapy moderated intervention effects, with women and participants receiving endocrine therapy experiencing greater improvements in health-related quality of life, fatigue, sleep disturbances, and strength. In addition, participants with poorer baseline health, including lower health-related quality of life, lower physical fitness, or higher fatigue, appeared to derive greater benefit.Study III explored cancer survivors' experiences of engaging in exercise within a live-remote format. In this qualitative study, 22 participants from the 12-week intervention took part in four online focus groups. Discussions were analysed using reflexive thematic analysis with an abductive approach, whereby themes were identified inductively and then mapped onto the Capability, Opportunity, Motivation (COM-B) model to help understand factors influencing exercise engagement. Nine themes were identified, reflecting exercise readiness following treatment, accessibility and professional support, peer support, life circumstances, the role of exercise in recovery and daily routines, caring for self and others, positive experiences exceeding expectations, and the development of exercise habits. From the participants' perspectives, live-remote exercise was seen to overcome barriers to participation and to provide both psychosocial and exercise support, thereby facilitating engagement and integration of exercise into daily life.In conclusion, this thesis demonstrates that a 12-week, live-remote supervised exercise intervention led to significant improvements in physical activity, physical function, fitness, and strength among cancer survivors. Although no significant effect was observed for overall health-related quality of life, meaningful gains were seen in the physical functioning domain. Most improvements observed post-intervention were not maintained at six months. Participants with lower health-related quality of life, reduced physical function, or higher fatigue at baseline appeared to derive greater benefit, as did female participants and those receiving endocrine therapy. Qualitative findings highlighted factors that facilitated exercise engagement, including professional supervision, accessibility, and the group format.Looking ahead, greater attention is needed on how virtually delivered exercise can be optimised to achieve benefits comparable to on-site interventions. Furthermore, strategies to help cancer survivors sustain exercise beyond the end of structured support will be essential to maintain long-term health gains. Taken together, these results suggest that live-remote, supervised exercise can support meaningful short-term health benefits, enhance engagement, and improve access to exercise for cancer survivors, thereby contributing to healthy survivorship.List of scientific papersI. Kotte M, Bolam KA, Altena R, Cormie P, Wengström Y, Mijwel S. Effects of live-remote exercise on quality of life and other health- related outcomes in cancer survivors: a randomised controlled trial. Journal of Cancer Survivorship. 2025. https://doi.org/10.1007/s11764-025-01845-xII. Kotte M, Mijwel S, Bolam KA, Altena R, Wengström Y. Who benefits most? Subgroup effects in a randomised controlled trial of live- remote exercise for cancer survivors. [Submitted]III. Kotte M, Ringborg CH, Wengström Y. The experience of live-remote exercise-perspectives after cancer treatment. Supportive Care in Cancer. 2024;32(8):526. https://doi.org/10.1007/s00520-024-08736-4